PENGGUNAAN TEKNOLOGI PENGINDERAAN JAUH DAN SISTEM INFORMASI GEOGRAFIS UNTUK MENGHITUNG PERSENTASE RUANG TERBUKA HIJAU DI DAERAH PERMUKIMAN KOTA DENPASAR - I Wayan Nuarsa (Bumi Lestari Journal of Environment, 2013)
AbstrakGreen open space (GOS) is a very important component in the arrangement of urban space,because the GOS has the function of ecological, aesthetic, social, cultural, and economic.Calculating of the GOS can easily be done in area that are enable for such purposes asurban forests, recreational areas of the city, as well as agricultural areas. However, for theland use consisting of non-GOS and GOS such as settlement, calculation of the GOS will bequite difficult. This research was conducted to measure the percentage of the GOS in settlementareas in the Denpasar city using remote sensing and geographic information systemtechnology. The results of this study showed that the percentage of the GOS in the settlementsarea of Denpasar ranged from 2.97% to 30.01%, with an average value of 14, 43%, and astandard deviation of 7.32% or 182.98 m2. The majority (50%) of the percentage of the GOSin the settlements area in the Denpasar city classified as moderate (10– 20%), 32% are low(<10%), and only 18% had a high percentage of the GOS (> 20%). Factors that influenceto the percentage of the GOS in the settlement area of Denpasar is the location of thesattements and the land area per housing unit.